Creation Marketing Capabilities As Antecedents For Success Marketing Performance - Sugiyarti, Gita (Journal of Research in Marketing (ISSN: 2292-9355), 2015)
SMEs as the backbone of the national economy and regional (ASEAN) contribute significantly to the national GDP and absorb as much as 97.2% of all workers in Indonesia. The purpose of this study was to analyze the influence of entrepreneurial orientation creativity, competence marketing knowledge and creation marketing capabilities to marketing performance. The population in this study, all small businesses in the city of Semarang Indonesia totaling 686 small industries. Sampling using purposive sampling method. Purposive sampling method is based on the technique of sampling with particular consideration, where the sample is selected with the conditions that are considered to have essential features that are relevant to the research. The samples were selected and qualified the small industry has a turnover and assets under 100 million, the number of workers 5-19 people, capital less than 25 million, totaling 115 respondents. The results of this study showed acceptable for variable influence creativity entrepreneurial orientation, competence marketing knowledge, creation of marketing capabilities, to marketing performance.